Taxonomic evaluation of marine gastropods along the Bay of Bengal (Zoological Records and Reviews, 2022)
The Bay of Bengal coastline, extending approximately 2,090 km along the eastern coast of India from West Bengal toTamil Nadu, encompasses highly diverse marine and intertidal habitats including rocky shores, sandy beaches, estuarinemudflats, seagrass beds, and coral reef patches. Marine gastropods (Class Gastropoda) constitute a major component ofthe benthic molluscan fauna in these habitats, performing critical ecosystem functions as grazers, predators, anddetritivores. Despite their ecological importance and commercial value, the gastropod fauna of the Bay of Bengal coast of India has not been comprehensively evaluated since the monographic work of Hornell and Tomlin (1934). This studypresents a systematic taxonomic evaluation of marine gastropods from 52 survey localities spanning the Indian Bay ofBengal coastline, sampled during 2019-2021 across four habitat types. A total of 312 gastropod species from 84 familiesand 148 genera are documented, including 48 new records for the Indian Bay of Bengal coast and 12 candidate newspecies. The families Muricidae (38 species), Conidae (34 species), and Cypraeidae (28 species) are the mostspecies-rich. Southern survey sites in Tamil Nadu show significantly higher species richness than northern sites in WestBengal and Odisha, consistent with the Indo-Pacific marine biodiversity gradient. Updated morphological diagnoses anddistribution maps are provided for all newly recorded species. Eighteen species are assessed as IUCN Threatened orNear Threatened, with overcollection for the ornamental shell trade identified as the primary conservation threat.
Keywords: Indian coast; new records; shell trade; Conidae; Muricidae; taxonomic evaluation; intertidal; marine molluscs; Bay of Bengal; Gastropoda